Elementy oceny charakteru zmian w prawie podatkowym - Huchla, Andrzej (Wydawnictwo Uniwersytetu Wrocławskiego, 2020)
Significant changes that have taken place in Polish tax law in recent years are primarily aimed at increasing budget revenues. This is done by improving efficiency and sealing the tax system by introducing new forms of burden and using subsequent taxpayer control mechanisms (including those modelled on solutions or recommendations of international importance). However, this is often done by way of frequent amendments, not based on the analysis of the effectiveness of earlier solutions, blurring the border between changes and introducing new taxes.
Keywords: tax law; changes in tax law; tax legislation